Digital Based Madrasah Head Leadership in Efforts to Improve Teacher Performance in State Madrasah Aliyah - Putra, Ridho Dwi; Murtadho, Muhammad Ali; Pertiwi, Fauza Yanuarti; Wigati, Indah; Karolina, Asri (Al-Fikru: Jurnal Ilmiah, 2025)
This study aims to analyze the influence of digital-based madrasah leadership on teacher performance at Madrasah Aliyah Negeri 1 Palembang. The study used a correlational quantitative method with a population of all teachers and madrasah principals, involving 45 teachers and 1 madrasah principal as respondents. Data were collected through questionnaires and analyzed using descriptive statistics and regression. The results show that the digital leadership of the madrasah principal is in the good to very good category, especially in terms of digital vision and technology-based communication indicators. Overall, teacher performance is classified as good, especially in digital learning planning and implementation, although teacher professional development still needs to be improved. Regression analysis showed a positive and significant influence between digital leadership and teacher performance (β = 0.62; p < 0.05), indicating that digital leadership improves learning effectiveness and teacher motivation. The novelty of this study lies in the integration of digital leadership with Islamic values, strengthening a technology-based work culture in madrasahs. These findings provide practical and theoretical contributions to the development of digital leadership in Islamic education.